Magnetic Composite Biomaterials for Neural Regeneration - Funnell, Jessica L.; Balouch, Bailey; Gilbert, Ryan J. (Frontiers in Bioengineering and Biotechnology, 2019)
Nervous system damage caused by physical trauma or degenerative diseases can result in loss of sensory and motor function for patients. Biomaterial interventions have shown promise in animal studies, providing contact guidance for extending neurites or sustained release of various drugs and growth factors; however, these approaches often target only one aspect of the regeneration process. More recent studies investigate hybrid approaches, creating complex materials that can reduce inflammation or provide neuroprotection in addition to stimulating growth and regeneration. Magnetic materials have shown promise in this field, as they can be manipulated non-invasively, are easily functionalized, and can be used to mechanically stimulate cells. By combining different types of biomaterials (hydrogels, nanoparticles, electrospun fibers) and incorporating magnetic elements, magnetic materials can provide multiple physical and chemical cues to promote regeneration. This review, for the first time, will provide an overview of design strategies for promoting regeneration after neural injury with magnetic biomaterials.